Maximizing Business Profit: A Perspective from Islamic Economic Law - Firdaus, Muhammad Irkham; Nasution, Saipul; Sup, Devid Frastiawan Amir (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2023)
Profit is the main goal taken by businessmen. The amount of profit earned is used as a measuring tool to evaluate the success of a business, so the profit earned must be higher than the cost of production. Nevertheless, there are business actors who take profits that are too large to be detrimental to consumers, so it is necessary to have a good profit standard, where the profits taken still benefit the businessman and not harm the consumer. So the profit taken must be fair and balanced with the cost of production taken. One of the characteristics of a capitalist economy is to minimize capital and obtain maximum profit. Whereas in Islamic economics the profit taken must be fair according to the capital issued. Islam is not specified, but a good profit does not exceed one -third of the capital. The concept of the goal of falah in Islamic business is problematic, and the ultimate goal is the good of the world and the hereafter. In this paper, we will discuss the law of maximizing business profits in Islamic Economic Law, as well as explain the concept of profit taking in Islam.